UK waste going forward : dialogue and decisions, One Great George Street Conference Centre, Westminster, London, 7 November 2001. (British Nuclear Energy Society, 2001)
This conference included topics such an overview of UK radioactive waste, long-term management of radioactive waste, experience at and expectations for Dounreay and community reaearch on improving the governance of nuclear waste management.